(untitled) (UNWE Yearbook, 2008)
The study is focused on the relationship between sustainable development and price and non-price competitiveness on the world market. We argue that this relationship is always positive in the long run because of two main reasons: first, any decrease in energy and material consumption per unit of product has double positive effects: (a) cost saving and (b) lower emission of pollutants. Second, goods with higher environmental parameters receive higher assessment from the consumers which improves the market positions of their producers and exporters.However, the same relationship has contradictive character in the short run. In principle, the environmentally friendly technologies and products suppose higher initial investments. It may lead to competitive disadvantage for some companies or even some national economies if their environmental standards are higher than the same standards in their trade partners. The author comes to the conclusion that sustainable development and market competitiveness could be mutually supportive if the WTO and other international bodies achieve certain harmonization of the environmental standards.